Low-frequency Elastic and Thermomechanical Analysis of Ni-Mn-In(Co) Single Crystals. (2015) - Villa, E.; Chernenko, V.A.; Cesari, E.; Lazpita, P.
Abstract: Martensitic transformation (MT) in Ni45.0 Mn36.7 In13.3 Co5.0 single crystals (SC) has been characterized by DSC and X-ray diffraction. Their elastic and thermomechanical properties have been investigated by a low-frequency dynamic-mechanical analysis in a tensile mode and by static mechanical compression made at different temperatures. The Young's modulus of the order of 10 GPa was measured in tensile tests along <100> crystallographic axis of austenite showing soft behavior in a broad temperature range whereby revealing a lattice instability similar to the classical Ni-Mn-Ga alloys. The compression tests along <100>, <011> and <111> directions have shown that despite a high brittleness the samples exhibit large martensitic plasticity, rubber-like behavior and superelasticity.